Future climate change scenarios differentially affect three abundant algal species in southwestern Australia. (May 2017) - Phelps, Charlie M.; Boyce, Mary C.; Huggett, Megan J.
Abstract: Three species of macroalgae ( Ecklonia radiata, Sargassum linearifolium, and Laurencia brongniartii ) were subjected to future climate change conditions, tested directly for changes in their physiology and chemical ecology, and used in feeding assays with local herbivores to identify the indirect effects of climatic stressors on subsequent levels of herbivory. Each alga had distinct physical and chemical responses to the changes in environmental conditions. In high temperature conditions, S. linearifolium exhibited high levels of bleaching and low maximum quantum yield. For E. radiata, the alga became more palatable to herbivores and the C:N ratios were either higher or lower, dependent on the treatment. Laurencia brongniartii was effected in all manipulations when compared to controls, with increases in bleaching, blade density, and C:N ratios and decreases in growth, maximum quantum yield, blade toughness, total phenolics and consumption by mesograzers. The differential responses we observed in each species have important implications for benthic communities in projected climate change conditions and we suggest that future studies target multi-species assemblage responses. Highlights: Three temperate macroalgae were exposed to future climate change scenarios. p CO2 and warming had species specific effects on algal physical/chemical ecology. Laurencia brongniartii had severely reduced performance under all treatments. For the semi-tropical Sargassum linearifolium, temperature, but not p CO2, had negative physiological impacts. Ecklonia radiata was physically resilient, but was more palatable to grazers.